Phenolic Compounds Isolated from Psoralea corylifolia Inhibit IL-6-induced STAT3 Activation - Lee, Seung Woong; Yun, Bo Ra; Kim, Mi Hwa; Park, Chan Sun; Lee, Woo Song; Oh, Hyun-Mee; Rho, Mun-Chual (Planta Medica, 2012)
Inhibiting interleukin-6 (IL-6) has been postulated as an effective therapy in the pathogenesis of several inflammatory diseases. In this study, seven flavonoids were isolated from the methanol extracts of Psoralea corylifolia by bioactivity-guided fractionation. The structures of bakuchiol (1), bavachinin (2), neobavaisoflavone (3), corylifol A (4), corylin (5), isobavachalcon (6), and bavachin (7) were determined by spectroscopic analysis (1H-, 13C- NMR and MS). We demonstrated that compounds 1–7 showed an inhibitory effect on IL-6-induced STAT3 promoter activity in Hep3B cells with IC50 values of 4.57 ± 0.45, 3.02 ± 0.53, 2.77 ± 0.02, 0.81 ± 0.15, 1.37 ± 0.45, 2.45 ± 0.13, and 4.89 ± 0.05 µΜ, respectively. These compounds also inhibited STAT3 phosphorylation induced by IL-6 in Hep3B cells. Overall, several flavonoids from P. corylifolia might be useful remedies for treating inflammatory diseases by inhibiting IL-6-induced STAT3 activation and phosphorylation.
Keywords: Psoralea corylifolia L.; Fabaceae; flavonoids; IL-6; STAT3; anti-inflammatory